Listeriosis en caprinos : reporte de un caso - Olguin Perglione, Cecilia; Fiorentino, María Andrea; Castillos, M.; Delgado, Fernando Oscar; Garbaccio, Sergio Gabriel; Schapiro, Javier Hernan; Morris, Winston Eduardo; Garro, Carlos Javier (Asosiación Argentina de Veterinarios de Laboratorios de Díagnóstico, 2022)
Poster y ponencia